The effects of the bank supervisory framework on bank performance: policy implications for Botswana based on a cross-country analysis of a group of African countries - Serero, Matlhodi M., author; Phillips, Ronnie, advisor; Jianakoplos, Nancy, committee member; Johnson, Richard, committee member; Mushinski, David, committee member (Colorado State University. Libraries, 2005)
Very few of the empirical studies used to determine the relationship between bank supervision and the performance of banks have included variables that explicitly capture bank regulatory or supervisory framework. This research is aimed at filling that shortage by empirically estimating the impact of the structure, the independence and scope of bank supervision on bank performance. Those variables are investigated alongside other determinants of bank profitability in the ordinary least squares models used to establish the impact of the supervisory framework on the performance of banks in Botswana and the rest of the sampled countries. As it is common in many other African countries, banking in Botswana is a very important industry in the mobilization of resources from savers to borrowers, hence banks play a critical role in funding investments that generate economic development and growth. Banks in Botswana are also important in providing a conduit through which the central bank can achieve its monetary policy objectives. Based on this importance of banks, the banking industry remains amongst the most highly monitored and regulated industries in Botswana and throughout the world. The primary objective of this thesis is to examine how bank profits and net interest margins respond to a supervisory authority which meets at least one of the following criteria; it operates in solitude, it is politically independent, its scope of responsibility extends to non-bank financial institutions and the central bank is either the supervisory authority or it is part of it. The findings of the research suggest that the existence of a single bank supervisor reduces the financial returns of banks, while the participation of the central bank in bank supervision improves profits and net interest margins of banks. Extending the scope of the supervisory authority to non-bank financial institutions and protecting the bank supervisor from political influence did not produce any significant results. Some regulatory variables that govern the activities of banks and institutions that conduct bank supervision were investigated. Regarding banks, a variable that allows for the investigation of how a tighter restriction on the mixing of banking with commerce impacts bank performance, was considered. Also, the relationship between bank performance and a variable that depicts the strict limitations on the cross-ownership between banks and non-bank financial institutions was assessed. A variable for explicit deposit insurance showed the influence of mandatory deposit insurance on the performance of banks. Finally, an investigation of the impact of the use of mandated subordinated debt in bank capital on bank profits and net interest margins was made. Among these variables, the strict control of ownership between banks and firms was detrimental to profits in terms of the returns on equity, while mandatory subordinated debt slightly enhanced net interest margins. The other two bank regulatory variables of the cross-ownership between banks and non-bank financial institutions and formal deposit insurance were insignificant. Discretionary power was the only regulation on bank supervisors included in the model and it produced insignificant results for all measures of bank performance. A general conclusion about the results suggests that regulations on banks represented by the tight restriction on mixing banking and commerce and the use of mandatory subordinated debt have an influence on bank profits and net interest margins. Furthermore, the structure of supervisory framework in terms of the participation of the central bank in supervision and the number of supervisors were shown to have a considerable effect on the performance of banks, while the independence and the scope of the bank supervisor were insignificant.
Keywords: investors; studies